: إدارة الوقف في جاوة الشرقية بإندونيسيا المشاكل والحلول في ضوء مقاصد الشريعة - كونتجورو، أرديكا وحيو (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This research aims to study the management of waqf in East Java, Indonesia, and the problems encountered in finding solutions based on the legal text and purposes (maqasid sharia). The study explored the concept of waqf in sharia and Indonesian law perspective and the researcher explained the importance of governance in the waqf management in achieving the professionalism of Nazir, then the research discussed the historical overview of the emergence of waqf management in East Java and the administrative problems that exist. The researcher adopted three approaches in this study: the inductive approach, analytical approach, and field study by conducting personal interviews with officials in East Java Province. Among the most important findings of the research are: The management and development of waqf in East Java was different before and after the enactment of Law No. 41 of 2004. Where officials faced some administrative problems, such as deficiencies in the waqf system and its legislations, lack of projects supporting its activities, the possibility of administrative corruption infiltrating the waqf institutions, the problem of property disappearance, and the professionalism of Nazir. And it was proposed to solve these problems by legislating an effective and contemporary waqf system, creating its projects, imposing accountability and transparency in its institution, preserving its properties, and employing professional Nazir to take care of it and achieve its purposes. The researcher also concluded that the waqf matters were broad and great, and the reward from Allah was also very great. It was sufficient that the reward lasts for the Waqif if the property exists, and its benefits increase and continue even after death. The researcher recommends that the central government pay more attention to waqf affairs by carrying out legal reforms and forcing local universities to hold seminars on professional waqf management.